Regenerative Endodontics Success Factors and their Overall Effectiveness: An Umbrella Review - Rojas-Gutiérrez, Wilder J.; Pineda-Vélez, Eliana; Agudelo-Suárez, Andrés A. (Iranian Endodontic Journal, 2022)
Introduction: Regenerative endodontics is a developing field of dentistry and aims to recover the physiological and anatomical functions of the tooth for cases of severe dental caries, pulpal pathologies and dental trauma. Materials and Methods: This umbrella review seeks to discover the scientific evidence on the effectiveness and the factors result in successful regenerative endodontic therapies in teeth with necrotic pulps and with incomplete root development. The study was conducted following the PRISMA Guidelines. There were no restrictions regarding search period. A comprehensive literature search was carried out in EMBASE, LILACS, PubMed, Cochrane, Scopus, and Google Scholar. A quality evaluation was conducted by using AMSTAR-2. A descriptive analysis of the included systematic reviews and meta-analysis were conducted. Results: Thirteen descriptive systematic reviews and 7 meta-analyses were included. Three articles evidenced low methodological quality according to AMSTAR-2 tool. Overall success rates for the endodontic regeneration procedures ranged from 50% to 98% and the survival rates were between 94% and 100%. Pulp regeneration had a high success rate, evidenced by factors such as the resolution of symptoms, healing, increased root length, dentin thickening and recovery of sensitivity. Follow-up varied from 1 to 48 months for the original studies included in the systematic reviews and meta-analyses. Conclusions: Endodontic practice offers the clinician a good treatment option in case of necrotic pulp with immature roots such as the endodontic regeneration, that is supported by high and moderate quality scientific literature.